Preparation, characterization, and biological activity study of thymoquinone-cucurbit[7]uril inclusion complex. Issue 4 (12th January 2022) - Alrawashdeh, Lubna; Assaf, Khaleel I.; Alshaer, Walhan; Odeh, Fadwa; Bani-Atta, Suhair A.
Abstract : The host–guest inclusion complexation of thymoquinone by cucurbit[7]uril in aqueous solution is established, which results in an enhanced biological activity. Abstract : In this study, the formation of a host–guest inclusion complex between cucurbit[7]uril (CB[7]) and thymoquinone (TQ) was investigated in aqueous solution. The formation of a stable inclusion complex, CB[7]–TQ, was confirmed by using different techniques, such as 1 H NMR and UV-visible spectroscopy. The aqueous solubility of TQ was clearly enhanced upon the addition of CB[7], which provided an initial indication for supramolecular complexation. The complexation stoichiometry and the binding constant of the inclusion complex were determined through a combination of two sets of titration methods, including UV-visible and fluorescence displacement titrations. Both methods suggested the formation of a 1 : 1 stoichiometry between CB[7] and TQ with moderate binding affinity of 3 × 10 3 M −1 . Density functional theory (DFT) calculations were also performed to verify the structure of the resulted host–guest complex and to support the complexation stoichiometry. The theoretical calculations were in agreement with experimental results obtained by 1 H NMR spectroscopy. Most importantly, the cytotoxic effect of the CB[7]–TQ complex was investigated against cancer and normal cell lines. The results showed that the anticancer activity of TQ against MDA-MB-231 cells was enhanced by the complexation with CB[7], while no significant effect was observed in MCF-7 cells. The results also confirmed the low toxicity of the CB[7] host molecule that supports the use of CB[7] as a drug carrier.